Development of a Technology Acceptance Model in Analyzing the Behavior of Muslim Traders Towards the Use of Quick Response Codes Indonesian Standard (QRIS) - Ilyas, Muhammad; Pulungan, Mardia; Denopan, Arian; Rinaldi, Nedi (International Journal of Science and Environment (IJSE), 2026)
The development of digital technology has encouraged the transformation of payment systems from cash transactions to non-cash transactions. One of the digital payment innovations in Indonesia is the Quick Response Code Indonesian Standard (QRIS) developed by Bank Indonesia to facilitate standardized digital payment transactions. This study aims to analyze the behavior of Muslim traders toward the use of QRIS by developing the Technology Acceptance Model / TAM introduced by Fred Davis. This research employs a quantitative approach using a survey method conducted among Muslim traders at Pasar Sangkumpal Bonang in Padangsidimpuan City. Data were collected through questionnaires distributed to respondents selected using a purposive sampling technique. The collected data were analyzed using statistical analysis to determine the relationship between the variables of perceived usefulness, perceived ease of use, attitude toward technology use, and behavioral intention to use the technology. The results indicate that perceived usefulness and perceived ease of use have a positive influence on traders’ attitudes toward using QRIS. These attitudes subsequently influence traders’ intentions to use digital payment technology in their trading activities. The findings of this study show that the perceived benefits and ease of use of technology are the main factors influencing the acceptance of QRIS among Muslim traders. This research is expected to contribute to the development of technology acceptance studies in the context of the digital economy and serve as a reference for stakeholders in increasing the adoption of QRIS among business actors.